Estudo eletroquímico de filmes finos de híbridos de polímeros conjugados e nanotubos de carbono para aplicação em dispositivos de armazenamento de energia - Glenda Ribeiro de Barros Silveira Lacerda (2020)
This work presents the synthesis and characterization of carbon nanotube (CNT) hybrids covalently bounded to conjugated copolymers formed by 3,4-ethylenedioxythiophene (EDOT) and pyrrole derivatives (pyrrole - Py, methylpyrrole - MPy and 3-(pyrrol-1- ylmethyl)pyridine - PyMP). The CNTs were functionalized in three stages, which consisted of their initial oxidation with sulfuric acid and concentrated nitric acid (3:1 v/v), followed by an amidation process (1,3-diaminopropane - DAP or tetraethylenepentamine - TEPA) and addition of the monomeric unit via thiophene carboxylic acid (TCA). Subsequently, copolymerization was used to form six new hybrids: CNT-TEPA-TCA-P(EDOT-co-Py) (H1), CNT-TEPA-TCA-P(EDOT-co-MPy) (H2), CNT-TEPA-TCA-P(EDOT-co-PyMP) (H3), CNT-DAP-TCA-P(EDOT-co-Py) (H4), CNT-DAP-TCA-P(EDOT-co-MPy) (H5) and CNT-DAP-TCA-P(EDOT-co-PyMP) (H6). All hybrids were characterized by spectroscopic techniques (Infrared - IR, Raman, and X-ray Photoelectron Spectroscopy - XPS), thermal (Thermogravimetry - TG) and morphological (Transmission Electron Microscopy - MET). The techniques used confirmed the coverage of the polymeric material throughout the CNT and their polymeric composition of approximately 45% by mass in the hybrid, corresponding to the molar formation of 1:1 CNT:conjugated copolymers. The studies of the electrochemical and electrical behavior of all hybrids were carried out, indicating their potential application as electrode material in supercapacitors (SCs), with their electrical conductivity results up to sixty times greater than the corresponding copolymer. The assemble of the complete devices (SCs) allowed us to analyze the versatility of the materials in different electrolytic media (acetonitrile and water), from a study with the H3 hybrid. The capacitances of the symmetrical cells obtained for SCs based on H3 were 56% and 115% higher than that of cells prepared with the unmodified NTC in organic and aqueous media, respectively. Complete cells also exhibited excellent cyclability with 81.3% (aqueous) and 77.5% (organic) capacitance retention after 5000 cycles. Another study carried out started with the comparison of hybrids (H5 and H6) with their precursor materials using aqueous LiClO4 solution as the electrolyte. The hybrids H5 (109.4 F g-1) and H6 (139.6 F g-1) synthesized showed an improvement in capacitance values compared to the pure CNT system (60.9 F g-1) and with the parent copolymers (69.2 F g-1 for P(EDOT-co-MPy) and 64.9 F g-1 for P(EDOT-co-PyMP)). The good retention of capacitance as a function of the current applied to the cells was also improved as a result of an improvement in charge transfer in the hybrids. The devices showed high performance with excellent cycling stability, compared to the low cycling of conjugated copolymers, even after 20000 cycles. The properties of the complete devices indicate the feasibility of the synthetic approach used, showing that the prepared hybrids are promising materials for use in highly cyclable supercapacitors.